Transformational and Ethical Leadership in Islamic Schools: Strengthening Teachers' Professional Ethics and Religious Character among Generation Z Students at MA Subhanah Subah Batang - Affix Ihsan Madani; M. Sugeng Solehuddin; Niken Rahmawati (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study examines the integration of transformational and ethical leadership in strengthening teachers' professional ethics and fostering the religious character of Generation Z students within the Islamic school environment. Employing a qualitative approach with an interpretive single-case study design, the research was conducted at MA Subhanah Subah Batang, Central Java, Indonesia. Data were collected through semi-structured interviews, participant observation, and document analysis, and subsequently analyzed using Reflexive Thematic Analysis. The findings reveal that the integration of both leadership styles produces a holistic organizational ecosystem, conceptualized as the "Transformational-Ethical Leadership Based on Uswah (T-EU) Model." This model strengthens teachers' professional ethics through value internalization and multi-layered exemplarity, transcending mere administrative compliance. Furthermore, authentic professional ethics transform into a primary catalyst in shaping the religious character of Generation Z students through the "Transformational-Ethical Exemplarity-Based Religious Character Formation (PKR-KTE) Model," which effectively navigates the challenges of digital disruption and contemporary moral crises. This study provides significant theoretical and practical contributions to the literature on Islamic educational leadership, asserting that value-based leadership is a fundamental prerequisite in responding to the complexities of character education in the modern era.